2018
DOI: 10.1016/j.surfcoat.2018.05.087
|View full text |Cite
|
Sign up to set email alerts
|

Black Co oxides coatings for thermosensitive polymer surfaces by low-temperature DLI-MOCVD

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao. Black coatings are deposited at low temperature in order to enable the functionalization of thermosensitive substrates, such as epoxy-based carbon fiber reinforced polymers (CFRP). The direct liquid injection metalorganic chemical vapor deposition of Co oxide films is performed with the dicobalt octacarbonyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…During this process, carbon black pigment plays a leading role in the electrolytic solution. Duguet et al [19] reported that black coating on thermosensitive polymer substrate at low temperatures ranging from 50 o C to 160 o C using direct liquid injection technology (DLI). Herein, cobalt oxide films are considered black coating and carbon fiber reinforced polystrate, respectively.…”
Section: Different Types Of Black Oxide Coatings and Its Characteriza...mentioning
confidence: 99%
“…During this process, carbon black pigment plays a leading role in the electrolytic solution. Duguet et al [19] reported that black coating on thermosensitive polymer substrate at low temperatures ranging from 50 o C to 160 o C using direct liquid injection technology (DLI). Herein, cobalt oxide films are considered black coating and carbon fiber reinforced polystrate, respectively.…”
Section: Different Types Of Black Oxide Coatings and Its Characteriza...mentioning
confidence: 99%
“…The use of a buffer layer was proposed to smoothen the microstructure. Previous studies of the authors indicate that cobalt could be a good candidate [32,33]. Although the interdiffusion between these two metals is almost null, Li et al used Co to promote the adhesion of the on-deposited Cu film in interconnected Cu/WN/SiO 2 multilayer assemblies [34].…”
Section: Introductionmentioning
confidence: 99%